Comparative proteomics evaluation of plasma exosome isolation techniques and assessment of the stability of exosomes in normal human blood plasma. Issue 22 (18th October 2013) - Kalra, Hina; Adda, Christopher G.; Liem, Michael; Ang, Ching‐Seng; Mechler, Adam; Simpson, Richard J.; Hulett, Mark D.; Mathivanan, Suresh
<x xml:space="preserve">Abstract</x> Exosomes are nanovesicles released by a variety of cells and are detected in body fluids including blood. Recent studies have highlighted the critical application of exosomes as personalized targeted drug delivery vehicles and as reservoirs of disease biomarkers. While these research applications have created significant interest and can be translated into practice, the stability of exosomes needs to be assessed and exosome isolation protocols from blood plasma need to be optimized. To optimize methods to isolate exosomes from blood plasma, we performed a comparative evaluation of three exosome isolation techniques (differential centrifugation coupled with ultracentrifugation, epithelial cell adhesion molecule immunoaffinity pull‐down, and OptiPrepTM density gradient separation) using normal human plasma. Based on MS, Western blotting and microscopy results, we found that the OptiPrepTM density gradient method was superior in isolating pure exosomal populations, devoid of highly abundant plasma proteins. In addition, we assessed the stability of exosomes in plasma over 90 days under various storage conditions. Western blotting analysis using the exosomal marker, TSG101, revealed that exosomes are stable for 90 days. Interestingly, in the context of cellular uptake, the isolated exosomes were able to fuse with target cells revealing that they were indeed biologically active.